2021
DOI: 10.1039/d1dt00809a
|View full text |Cite
|
Sign up to set email alerts
|

Two three-dimensional polyanionic clusters [M(P4Mo6)2] (M = Co, Zn) exhibiting excellent photocatalytic CO2 reduction performance

Abstract: Two captivating {P4Mo6}-based compounds, formulated as (H2bbi)2{[Co2(bbi)][Co(H2O)2]2[Co(H5P4Mo6O31)2]}·4H2O (1) and (H2bbi){[Zn(Hbbi)]2[Zn(bbi)][K2Zn(H2O)4][Zn(H4P4Mo6O31)2]} (2) [bbi = 1,1'-(1,4-butanediyl)bis(imidazole)] were successfully synthesized under hydrothermal conditions. Structural analysis demonstrates that compounds 1 and 2 are constructed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Hence, it is vital to develop reductive CO 2 photocatalysts with high efficiency, high selectivity and low cost for facilitating this reaction process. 12–21…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, it is vital to develop reductive CO 2 photocatalysts with high efficiency, high selectivity and low cost for facilitating this reaction process. 12–21…”
mentioning
confidence: 99%
“…Hence, it is vital to develop reductive CO 2 photocatalysts with high efficiency, high selectivity and low cost for facilitating this reaction process. [12][13][14][15][16][17][18][19][20][21] Polyoxometalates (POMs), as a kind of inorganic metal oxygen cluster with redox properties and excellent multi-elec-tron transfer ability, have been subject to extensive studies in numerous domains, such as medicine, [22][23][24] optics, [25][26][27] catalysis, [28][29][30][31][32][33][34][35] electrochemistry, [36][37][38][39][40] etc. Among plenty of POMbased clusters, molybdenum(V) cobalto-phosphate clusters have been considered as prospective promising photocatalysts for CO 2 reduction owing to the presence of reduced Mo V and Co II 42 Although some achievements have been made, there are no reports on isolated inorganic wheellike cobalto-phosphate clusters as CO 2 reduction reaction (CO 2 RR) catalysts until now.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, when we replaced {Zn-CrMo 6 } with {Co-CrMo 6 } , the amount of CO could reach 77.4 μmol (turnover number (TON) = 23.8) accompanied by the high selectivity (92.6%) of CO over H 2 and CH 4 (Table S1). The reason for different phenomena is probably that cobalt ions can offer more catalytically active sites to drive CO 2 conversion in view of the same combining circumstance of two POM-based MOCs. , …”
Section: Resultsmentioning
confidence: 99%
“…Among the family of POMs, the reduced hourglass-type {M­[P 4 Mo V 6 O 31 ] 2 } n − (abbr. M­{P 4 Mo 6 } 2 ) polyoxoanionic cluster possesses a high negatively charged surface with all Mo atoms in the +5 oxidation state, which endows the assembled M­{P 4 Mo 6 } 2 cluster with a peculiar reversible redox feature and wide visible-light absorption capacity. Moreover, the electron structure of M­{P 4 Mo 6 } 2 is flexible and tunable, and can be easily manipulated by adjusting the central metal species, providing the possibilities for the exploitation of high-efficient photocatalysts. At present, hourglass-type M­{P 4 Mo 6 } 2 photocatalysts have been applied in some photocatalytic process, for example, the photocatalytic degradation of organic dyes, photocatalytic reduction of organic compounds (such as p -nitrophenol), photocatalytic conversion of CO 2 to CH 4 , and so on. Our previous work preliminarily explored the photocatalytic performance of M­{P 4 Mo 6 } 2 -based compounds for Cr­(VI) reduction, and found that the crystal stacking arrangement and conjugated organic components have an effect on the photocatalytic Cr­(VI) reduction activity. Although significant progress has been made so far, the highly efficient M­{P 4 Mo 6 } 2 -based photocatalysts still need to be explored and the structure–performance relationship between hourglass-type POMs and their photocatalytic performance toward Cr­(VI) reduction still needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%